Pseudokiefferiella ferringtoni sp. nov. (Diptera: Chironomidae: Diamesinae) from North America - Makarchenko, Eugenyi A. (Zootaxa, 2024)
In this article I continue to publish the data obtained as a result of the revision of the subfamily Diamesinae, namely of the genus Pseudokiefferiella Zavřel, 1941. As we noted earlier (Makarchenko & Semenchenko 2023), before the start of molecular genetic study this genus was considered as monotypic, that is, with one species of Ps. parva (Edwards) in Holarctic region (Ashe & O’Connor 2009). According to work of Stur and Ekrem (2020), as well as the results of our research and data of GenBank, there are at least 6 species in the genus Pseudokiefferiella that are well separated by DNA barcoding, while adult males poorly differ morphologically. However, species of this genus can be successfully identified by the morphological structures of the pupa, if it is associated with a male imago. As confirmation of this, below is provided a description of Pseudokiefferiella ferringtoni sp. nov. from North America based on the adult male and pupa, in which the originality of a new species is corroborated by the morphological structures of the pupa.